Transformasi Digital Pelaku UMKM dan Kesesuaiannya dengan Etika Bisnis Syariah di Kawasan Pantai Panjang Kota Bengkulu - Nadia Ananda Putri; Romi Adetio Setiawan; Nurrahmah Putry (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2026)
Digital transformation has become a crucial strategy for Micro, Small, and Medium Enterprises (MSMEs) to enhance their competitiveness in the era of information technology advancement. The use of social media, marketplaces, digital payments, and various online platforms provides opportunities for MSMEs to expand their marketing reach and improve business efficiency. However, the implementation of digital transformation also requires adherence to the principles of Islamic business ethics, such as honesty, trustworthiness, fairness, and transparency in all business activities. This study aims to analyze the digital transformation practices undertaken by MSMEs in the Panjang Beach area of ​​Bengkulu City and assess their compliance with Islamic business ethics. The study employed a qualitative descriptive approach with field research methods. Informants were selected through purposive sampling, involving MSMEs actively utilizing digital technology in their business activities. Data were collected through observation, in-depth interviews, and documentation, then analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results are expected to provide an overview of the implementation of digital transformation in MSMEs and its level of compliance with the principles of Islamic business ethics. Furthermore, this research is expected to serve as a reference for MSMEs in developing digital-based businesses that are not solely focused on economic profit but also adhere to Sharia values ​​in their business practices.